2019
DOI: 10.3390/d11080140
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities from Extreme Environments: Vulcano Island

Abstract: Although volcanoes represent extreme environments for life, they harbour bacterial communities. Vulcano Island (Aeolian Islands, Sicily) presents an intense fumarolic activity and widespread soil degassing, fed by variable amounts of magmatic gases (dominant at La Fossa Crater) and hydrothermal fluids (dominant at Levante Bay). The aim of this study is to analyse the microbial communities from the different environments of Vulcano Island and to evaluate their possible correlation with the composition of the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…3 ). This was consistent with the findings of previous studies that examined bacterial communities at the phylum level, such as Proteobacteria, Actinobacteria , and Firmicutes ( Singh et al , 2014 ; Fagorzi et al , 2019 ). Several members of these phyla exist in various environments, confirming their capacity to adapt to a wide range of environments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3 ). This was consistent with the findings of previous studies that examined bacterial communities at the phylum level, such as Proteobacteria, Actinobacteria , and Firmicutes ( Singh et al , 2014 ; Fagorzi et al , 2019 ). Several members of these phyla exist in various environments, confirming their capacity to adapt to a wide range of environments.…”
Section: Discussionsupporting
confidence: 93%
“…Another study provided insights into the spatial distribution of microbial communities at high elevations in a volcanic zone ( Solon et al , 2018 ). A geo-microbiological approach was recently applied to volcanic soils and pioneer plants ( Fagorzi et al , 2019 ).…”
mentioning
confidence: 99%
“…Extreme environments that yield high salinity, low a w , and radiation tolerance, among others ( Table 1 ), will have specialized gene expression that tolerates the aforementioned extreme properties. Typically, these ecosystems have a lower microbial diversity than nominal/nonextreme settings due to lower adaptability of microorganisms and tolerant gene expressions that would allow the ongoing maintenance of these biological processes (Summons et al , 2008 ; Msarah et al , 2018 ; Chaya et al , 2019 ; Fagorzi et al , 2019 ; Gugliandolo and Maugeri, 2019 ).…”
Section: Nomenclature and Definition Setsmentioning
confidence: 99%
“…These changes in the chemical composition at least partially explain the progressive but marked decrease in bacterial diversity as we approached the Roman fort, resulting in the dominance of two taxa in the soils inside the fort. Over‐representation (>75%–85%) of one genus or species in an ecosystem is rare, even in extreme environments (Fagorzi et al, 2019; Frindte et al, 2019) and, to our knowledge, is only found in very specific ecological niches such as grape‐must fermentation, with the spontaneous dominance of the Saccharomyces genus (Guzzon et al, 2022). These unexpected results strongly suggest that the construction of the Roman fort and its human occupancy for four centuries have lastingly modified the soil of this dryland ecosystem, even after 1500 years of human absence.…”
Section: Discussionmentioning
confidence: 99%